Chemical and Microscopy Characterization of Trans-Endodontic Implants - Larios-Cervantes DDS, Alexis (2018)
Trans-endodontic implants are an artificial extension through root apex anchored in periradicular bone tissue. The aim is to improve the crown-root ratio and to provide stability to dental organ present. Zirconium oxide (ZrO2) is a material of great technological importance, having good natural color, high strength, high toughness, high chemical stability, does not suffer any corrosion, chemical and microbial resistance and excellent esthetic properties.  Objective: The aim of this study was to evaluate chemical and microscopy of surface conditions of ZrO2 trans-endodontic implant. Materials and Methods: A blocks of ZrO2 were manufactured for produce trans-endodontic implants and divided in two groups: monoclinic and tetragonal phase. They were evaluated using Scanning Electroning Microscope (SEM), Energy-Dispersive X-ray Spectroscopy (EDS), and Atomic Force Microscope (AFM) and Vickers Micro hardness. Results: The Monoclinic phase through AFM analysis showed roughness Ra = 0.320μm, whereas in the Tetragonal phase was 0.126μm, SEM/EDX indicated that the phases are not properly uniform and the addition of the Yttrium to favor the stabilization of the Tetragonal phase. The Vickers hardness analysis showed a value of 1500HV.  Conclusion: The characterization of the surface of trans-endodontic zirconium oxide implants provides a guideline to know the surface characteristics of the material, since a greater roughness on the surface of the implant will favor the Osseo-integration capacity.